Environmental risk analysis (ERA) in the strategic asset allocation (SAA) of the international reserves (IRs) managed by central banks (CBs) - Viviane Helena Torinelli; Antônio Francisco Silva Júnior (Latin American Journal of Central Banking (LAJCB), 2021)
This study addresses how to consider environmental risk analysis (ERA) in the strategic asset allocation (SAA) of international reserves (IRs) managed by central banks (CBs). For that, a multicriteria analytical framework is proposed for the evaluation of the environmental risk exposure of an investment portfolio, compatible with the investor profile of the CBs. Thus, the framework includes ERA in the traditional SAA approach of IRs. Environmental risks, as physical and transition climate ones, are resulting in a range of financial risks, but ERA is still incipient in the financial investment sphere, especially among CBs. Reports of the NGFS and NGFS members were reviewed, and we found no specific indication of ERA as an input on SAA of the IRs. Thus, the main argument of this study is that since ERA is included in the traditional approach to SAA, IRs investments will be more resilient to environmental and climate risk exposure. The framework discussed in this paper suggests that for each viable portfolio, a CB should use scenarios of environmental risks along with probabilities and potential impacts to choose the appropriate portfolio. The risk and return relationships of the portfolios in each scenario should be evaluated based on environmental factors.
Keywords: G11; G15; 330; Central banks; Environmental risk analysis; International reserves; Strategic asset allocation